2015
DOI: 10.1016/j.arcmed.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

QT Indexes in Cirrhotic Patients: Relationship with Clinical Variables and Potential Diagnostic Predictive Value

Abstract: Background and Aims. A wide spectrum of cardiovascular changes characterizes cirrhosis, ranging from subclinical alterations to hyperkinetic syndrome. We looked for ECG markers of ventricular repolarization in a population of patients with cirrhosis in comparison to patients without cirrhosis and we investigated the relationship between these and other clinical and laboratory variables. Methods. In 149 patients with cirrhosis and 152 controls, we measured QT maximum interval (QTmax), QT corrected interval (QTc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
5
1
Order By: Relevance
“…[13][14][15] QT indexes are altered in cirrhotic patients and have a potential diagnostic predictive value. 16 In our study, although within normal limits, a statistically significant prolongation of QTc interval was shown in patients with compensated cirrhosis compared to the control group. The lack of overcoming of the pathological limits of QTc was thought to be due to the patients' good functional capacity and cardiomyopathy not being yet developed.…”
Section: Discussioncontrasting
confidence: 46%
“…[13][14][15] QT indexes are altered in cirrhotic patients and have a potential diagnostic predictive value. 16 In our study, although within normal limits, a statistically significant prolongation of QTc interval was shown in patients with compensated cirrhosis compared to the control group. The lack of overcoming of the pathological limits of QTc was thought to be due to the patients' good functional capacity and cardiomyopathy not being yet developed.…”
Section: Discussioncontrasting
confidence: 46%
“…Herein we found that both dQT and dQTc were more prolonged in patients with cirrhosis. One previous study has shown that QT and dQt is prolonged in patients with cirrhosis[ 29 ], while another study shown that QT, but not dQT, is prolonged in patients with alcoholic cirrhosis in comparison with controls[ 30 ]. In contrast, in another study, no differences were found in dQT between patients with cirrhosis and controls[ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 While abnormal QTc dispersion, in general, can be seen as an early marker of myocardial damage, patients with decompensated cirrhosis often have increased QTc dispersion possibly related to their cardiovascular impairment. 14,71 Chronotropic incompetence means that cirrhotic patients cannot adequately increase their heart rate in response to different stimuli, such as exercise or drugs, contributing to the limited increase of cardiac output and exercise capacity. 1 When contractility is compromised, heart rate has an important contribution to cardiac output, which cannot adequately adapt to stress or effort.…”
Section: Electrophysiological Abnormalitiesmentioning
confidence: 99%